Investimento em empresas brasileiras de capital aberto: um estudo da variável q de Tobin, como medida de avaliação das oportunidades de investimento pós-plano real. - Igor Vasconcelos Nogueira (2010)
The value optimization of the company drives the decisions and the behavior of your manager. Similarly, decisions of outside investors, which were characterized by not having a relationship with company management, are directed to maximize return and minimize the risk of their investments. On investment opportunities, both managers and outside investors using valuation models to reduce the uncertaintyof future earnings. Therefore, this research sought to answer if Tobin's q indicator - an indicator for evaluating companies based on the market - is relevant in investment opportunities analysis for manager and outside investor in Brazilian companies in the post-Real Plan. To resolve this issue, this research measured and analyzed the behavior of Tobin's q and investment for 137 Brazilian joint-stock companies and that have participated in the Bovespa index between 1994 and 2009. There was also, training strategies of investment portfolios with Tobin's q,implied relationships more profitable return to investors. It were estimated panels data empirical models to see if the variable Tobin's q is significant to the level of investment, determined by manager. The results indicated that Tobin's q value was significant to investment opportunities. The relevance in the analysis of investment opportunities for outside investors was confirmed by observing a more profitable return in the short term, for portfolios of assets with higher values of q and a moreadvantageous risk-return in the medium and long term, for portfolios of assets with lower values of q. The relevance of the indicator Tobin's q, an analysis of investment opportunities for the manager, was confirmed through its significance in an empirical model for the level of investment by Brazilian companies traded in the post-Real Plan.